Increased Incidence of Stunting Due to Pesticide Exposure in Agricultural Areas - Putri, Shafira Anindyah; Setyowati, Putri Sari Retno; Elizah, Putri Nur; Silvia, Mega; Kurniyawan, Enggal Hadi (Jurusan Kebidanan Poltekkes Kemenkes Padang, 2024)
Children who grow up in agricultural areas have a risk of experiencing stunting or developmental disorders due to exposure to pesticides, which can be one of the factors for stunting. This study aimed to determine the side effects of pesticide exposure on the incidence of stunting in agricultural areas. The method used in writing this research is a literature review using keywords on Google Scholar